Oncology pharmacy practice: The clinical pharmacist's perspective - (:unkn) unknown (Nova Science Publishers, Inc., 2021)
Incidence of cancer is increasing all over the world and personalized therapies have become the trend in cancer therapy. Multidisciplinary approaches provide successful results for personalized therapies. As a part of a multidisciplinary healthcare team, oncology pharmacists (OPs) contribute to the rational use of chemotherapy by providing individual pharmaceutical care for cancer patients. A multidisciplinary approach is crucial for the success of cancer therapy. Pharmacists acting as a counsellor for medication-related issues in the multidisciplinary team have a vital role in the oncology setting. OPs are the clinical pharmacists specialized in oncology and they are involved in planning and implementation of pharmaceutical care. Additionally, OPs play an important role in providing comprehensive medication management and related care for cancer patients. We hope that this book will contribute to pharmacists' knowledge and practice in cancer management by provision of a clinical pharmacist's perspective. © 2021 Nova Science Publishers, Inc. All rights reserved.